FAKTOR INTERNALYANG MEMPENGARUHI HASIL BELAJAR MAHASISWA MATA KULIAH SURVEY DAN PEMETAAN PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FT-UNP - Ardimansyah .; Fahmi Rizal; Iskandar G Rani (CIVED, 2018)
Abstract—This research begins with the problem of low student learning outcomes on Survey and Mapping subject. Based on the problem, we conducted this study the main purpose of this study is to   determine what is the most dominant internal factors which give effect to student learning outcomes in the subject of Survey and Mapping at education Building study Program FT UNP. This type of research  descriptive quantitative. The population in this study  the students who take the Survey and mapping courses from July to December 2015 and 2016 which consist of 166 students. Samples were taken using Total Sampling technique. Technique of collecting data using questionnaire with likert scale. Questionnaire in this research a questionnaire about internal factors that affect student learning outcomes. The technique of data analysis using descriptive analysis by calculating the percentage of each subindicator using the formula of degree of achievement (DP). The conclusion of this research shows that health factor the most dominant factor influencing student learning outcomes of Study Program of Building Engineering Education Department of Civil Engineering Faculty of Engineering State University of Padang with degree achievement of  80,31% with big scoring category. Keywords: Internal Factors, Learning Outcomes, Survey and Mapping